Optimizing Teacher Evaluation: Development of a Digital-Based Curriculum Training Instrument for Enhanced Feedback - Aisyah Yuspita Hamrul; Sukirman; Dodi Ilham (Al-Qalam Institue, 2025)
Evaluation instruments in teacher training are important elements to ensure the improvement of teaching competence and the effectiveness of the learning process. With the development of technology, digital-based evaluation instruments have emerged as a solution to provide faster and more accurate feedback. However, the use of technology in training evaluation still faces challenges, such as limited digital skills among some teachers. This study aims to develop a digital-based evaluation instrument and analyze its impact on teacher competency development. The approach used in this study is qualitative with a case study design, through in-depth interview techniques, participatory observation, and documentation studies. The results of the study indicate that digital-based evaluation instruments have a positive impact on teacher competency development by accelerating the process of self-reflection and improving teaching techniques. However, challenges related to technical limitations in some teachers require attention to ensure the effectiveness of using this instrument. These findings emphasize the importance of technology training to support continuous teacher professional development.